α-LiFe5O8 as the cathode of a supercapacitor integrated in a three-electrode photo-supercapacitor - Peinado-Pérez, Juan José; Martín-Jiménez, Francisco de Paula; López-Escalante, María Cruz (ELSEVIER, 2025)
This study investigates the use of lithium ferrite α-LiFe5O8 (LFO) thin film electrodes as cathodes in both asymmetric supercapacitors (ASC) and three-electrode photo-supercapacitors (PSC). The nature of the electrolyte plays a fundamental role in these systems. Therefore, LFO was characterised in a three-electrode electrochemical cell using two aqueous solutions: 0.5 M Na2SO4 and 0.5 M LiClO4, yielding specific capacities of 119 and 70 F g−1, respectively, at a current density of 0.5 A g−1. LFO was then assembled in an ASC with a ZnMn2O4 electrode as the anode, and the influence of two different electrolytes was studied: an aqueous solution of 0.5 M Na2SO4 and a polymer gel containing polyvinyl pyrrolidone (PVP) and LiCLO4. The ASCs exhibited distinct behaviour depending on the electrolyte used. The device response shifted from that of a pseudocapacitive supercapacitor (Na2SO4) to that of a hybrid supercapacitor (PVP–LiClO4). ASC devices containing Na2SO4 or PVP–LiClO4 electrolytes exhibited maximum specific capacitances of 52 and 64 F g−1, respectively, at a current density of 0.5 A g−1; the corresponding energy densities were 13 and 32 Wh kg−1, power densities were 237 and 473 Wh kg−1, and capacity retention were 20 % and 50 %, respectively. Three-electrode PSCs were prepared by integrating a dye-sensitised solar cell into the power generation system. The highest performances were obtained under low irradiance, with storage and overall efficiencies of 43.20 % and 1.46 %, respectively.
Keywords: Ingeniería química; Electroquímica; Energía - Almacenamiento; Condensadores (Electricidad); Electrólitos; Materiales - Propiedades eléctricas; Electrolyte nature; Supercapacitor; Photo-supercapacitor; Indoor environment